2019
DOI: 10.1177/1708538119828887
|View full text |Cite
|
Sign up to set email alerts
|

The endovascular repair of blunt traumatic thoracic aortic injury in Asia: A systematic review and meta-analysis

Abstract: Introduction Blunt traumatic thoracic aortic injury, the second leading cause of death from trauma, poses unique challenges in its management. However, there has not yet been a corresponding consolidated series of outcomes reported in Asia, which this systematic review aims to address. Method This review was performed as per the Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines. Searches were performed on MEDLINE, EMBASE, Google Scholar, and Cochrane Database for studies performed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 37 publications
0
14
0
1
Order By: Relevance
“…15 Current recommendations in the literature limit maximum oversizing to 20%. 16 The size of the endografts used and their positioning are determinant factors in the post-treatment results. García Reyes et al 15 observed that patients who exhibited complications related to endografts had greater oversizing than a subset free from complications (p = 0.0007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Current recommendations in the literature limit maximum oversizing to 20%. 16 The size of the endografts used and their positioning are determinant factors in the post-treatment results. García Reyes et al 15 observed that patients who exhibited complications related to endografts had greater oversizing than a subset free from complications (p = 0.0007).…”
Section: Discussionmentioning
confidence: 99%
“…15 The majority of devices currently available are not specifically designed for traumatic injuries to the aorta, and it is difficult to find the smaller sizes that would be ideal for younger patients. 16 This obliges many surgeons to implant endografts with greater oversizing, as the only viable option for endovascular treatment. However, excessive oversizing can be related to type I endoleak and kinking and collapse of endografts.…”
Section: Discussionmentioning
confidence: 99%
“…Aortic injuries are associated with mechanisms involving penetrating and blunt trauma. Blunt traumatic aortic injuries (BTAI) of the thoracic aorta account for the second greatest cause of traumatic deaths with a significant impact to function amongst survivors [ [2] , [3] , [4] ]. Injuries occur mainly due to rapid deceleration with high-energy impact to the thorax, often involving motor vehicle and aircraft collisions, assaults, crush injuries and falls from significant heights [ 2 , 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Blunt traumatic aortic injuries (BTAI) of the thoracic aorta account for the second greatest cause of traumatic deaths with a significant impact to function amongst survivors [ [2] , [3] , [4] ]. Injuries occur mainly due to rapid deceleration with high-energy impact to the thorax, often involving motor vehicle and aircraft collisions, assaults, crush injuries and falls from significant heights [ 2 , 3 ]. Patients at greater risk of BTAI in vehicle collisions are those aged 60 years or older, unrestrained, or occupants of front seats [ 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chest trauma is the second leading cause of trauma-related deaths, accounting for 20-25% of all trauma-related deaths (1). Multiple rib fractures, especially in patients with flail chest, are often accompanied by severe pain, chest wall softening, abnormal breathing and severe lung contusion.…”
Section: Introductionmentioning
confidence: 99%